Investigating Ugi/Passerini Multicomponent Reactions for the Site‐Selective Conjugation of Native Trastuzumab. Issue 61 (21st September 2020) - Sornay, Charlotte; Hessmann, Steve; Erb, Stéphane; Dovgan, Igor; Ehkirch, Anthony; Botzanowski, Thomas; Cianférani, Sarah; Wagner, Alain; Chaubet, Guilhem
Abstract: Site‐selective modification of proteins has been the object of intense studies over the past decades, especially in the therapeutic field. Prominent results have been obtained with recombinant proteins, for which site‐specific conjugation is made possible by the incorporation of particular amino acid residues or peptide sequences. In parallel, methods for the site‐selective and site‐specific conjugation of native and natural proteins are starting to thrive, allowing the controlled functionalization of various types of amino acid residues. Pursuing the efforts in this field, we planned to develop a new type of site‐selective method, aiming at the simultaneous conjugation of two amino acid residues. We reasoned that this should give higher chances of developing a site‐selective strategy compared to the great majority of existing methods that solely target a single residue. We opted for the Ugi four‐centre three‐component reaction to implement this idea, with the aim of conjugating the side‐chain amine and carboxylate groups of two neighbouring lysine and aspartate/glutamate. Herein, we show that this strategy can give access to valuable antibody conjugates bearing several different payloads; furthermore, the approach limits the potential conjugation sites to only six on the model antibody trastuzumab. Abstract : Payload delivery : Ugi and Passerini reactions were found to be effective strategies for the conjugation of native trastuzumab. The use of functionalized aldehydes and isocyanides allows for the smooth introduction of various payloads onto the antibody, including the cytotoxic drug MMAE.